Hubungan Pengetahuan Dan Dukungan Keluarga Dengan Kunjungan Ibu Nifas Di Wilayah Kerja Puskesmas Tanjung Leidong Kabupaten Labuhan Batu Utara - Askinah Askinah; Lasria Simamora (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Based on data on the health profile of North Sumatra, coverage of complete postpartum maternal health services (KF3) in 2019 was 81.50%, this target has not yet reached the target set in the North Sumatra Provincial Health Service Strategic Plan for 2019, namely 84%. Where one of the districts/cities whose KF3 achievement in its area has not reached 84% as stated in the 2019 North Sumatra Provincial Health Service Strategic Plan target is North Labuhan Batu district, namely 80.02% (North Sumatra Health Service, 2019). This postpartum service aims to assess the status of the mother and newborn as well as to prevent, detect and treat problems that occur. Postpartum maternal visits are the behavior of postpartum mothers visiting health services to obtain health services. This behavior is influenced by knowledge and family support. The author aims to analyze the relationship between husband's knowledge and support and postpartum visits in the Tanjung Leidong health center work area in 2022. The type of research is correlational research with a quantitative approach carried out in March - June 2022. The population in this study is all postpartum mothers in the work area Tanjung Leidong Public Health Center, North Labuhan Batu Regency in 2022, there are 33 people. The sampling technique in this research is Consecutive sampling. The data analysis technique used is Spearman's Rho Correlation with a significance level of 5% (95% confidence level). The research results show that knowledge has a significant relationship with postpartum visits with a p value of 0.09 <0.05. Meanwhile, family support does not have a significant relationship with postpartum visits with a p value of 0.21>0.05. It is hoped that health workers will hold Communication, Information and Education (KIE) activities to increase the knowledge of postpartum mothers in carrying out postnatal examinations. With this activity, the knowledge, attitudes and motivation of postnatal mothers can increase in carrying out postnatal examinations so that it will improve the performance of midwives in postnatal examinations.